2002
DOI: 10.1080/00984100290071045
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Administration Affects Plasma Total Sialic Acid and Lipid Peroxidation Levels in Streptozotocin Induced Diabetic Rats

Abstract: Administration of streptozotocin (STZ) was used to induce diabetes, as the mechanism involved is believed associated with generation of free radicals. Supplementation with antioxidant molecules such as melatonin may serve as a protection against diabetes. The aim of this study was to determine whether the STZ-induced effects on plasma thiobarbituric acid-reactive substances (TBARS, a marker of lipid peroxidation) and total sialic acid levels could be blocked by melatonin. STZ significantly increased the plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 15 publications
4
6
0
Order By: Relevance
“…The endogenous overexpression or mislocalization of sialidases induced by an unknown factor may be proposed as an interesting hypothesis. In this framework, several studies have reported impaired sialylation related to oxidative stress22232425. Oxidant injury/free radical reactions observed in diabetes, malignancy, and aging can cause desialylation and carbonylation of platelet proteins in vitro 22.…”
Section: Discussionmentioning
confidence: 99%
“…The endogenous overexpression or mislocalization of sialidases induced by an unknown factor may be proposed as an interesting hypothesis. In this framework, several studies have reported impaired sialylation related to oxidative stress22232425. Oxidant injury/free radical reactions observed in diabetes, malignancy, and aging can cause desialylation and carbonylation of platelet proteins in vitro 22.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, streptozotocin-induced diabetes increases oxidative stress through generation of free radicals [87] , lipid peroxidation, superoxide dismutase, protein glycosylation [88] , decreased levels of catalase and glutathione peroxidase [89] , as well as DNA single-strand breaks [85] . In the serum of animals with streptozotocin-induced diabetes, melatonin remarkably reduces the degree of both lipid peroxidation and protein glycosylation [88] , decreases the levels of cholesterol, triglyceride, low-density lipoprotein [90] , sialic acid [91] and glucose [92] , as well as possibly regulating the activities of antioxidant enzymes [89] . Nevertheless, the most pronounced effect of melatonin administration was the prevention of an increase in NO levels in blood plasma during streptozotocin-induced diabetes [93] , which implies that melatonin may operate as an NO scavenger and carrier.…”
Section: Melatonin Modulates Diabetes-related Alterationsmentioning
confidence: 99%
“…12 Consequently, many researchers reported that diabetes increased lipid peroxidation in experimental animals. [20][21][22] In any case, diabetes is used as a model of oxidative damage in experimental animals. 12,22 Elevated MDA levels we obtained in the brain tissue of the diabetes group (Group 8), which was not subjected to any additional procedure, are consistent with the results of the above-cited researchers.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] In any case, diabetes is used as a model of oxidative damage in experimental animals. 12,22 Elevated MDA levels we obtained in the brain tissue of the diabetes group (Group 8), which was not subjected to any additional procedure, are consistent with the results of the above-cited researchers. However, in the present study, we established the highest brain MDA values in the diabetes group subjected to swimming exercise (Group 7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation